Controlled anisotropic wetting of scalloped silicon nanogroove. Issue 48 (27th April 2016) - Kim, Gun-Hee; Lee, Byung-Hyun; Im, Hwon; Jeon, Seung-Bae; Kim, Daewon; Seol, Myeong-Lok; Hwang, Hyundoo; Choi, Yang-Kyu
Abstract : The anisotropic wetting characteristics of SNGs were investigated in dynamic and static regimes. The anisotropic wettability of the SNGs was successfully employed to control fluid flows in microfluidic channels. Abstract : The anisotropic wetting characteristics of scalloped nanogrooves (SNGs) were investigated for the first time. SNGs with various scallop edge angles were fabricated by Bosch deep reactive ion etching (DRIE). The wetting properties of the nanopatterned surfaces were studied in dynamic and static regimes. The anisotropic wettability of the SNGs was successfully employed to control fluid flows in microfluidic channels.